PENGARUH DAU, DAK, JUMLAH PENDUDUK DAN LUAS WILAYAH TERHADAP BELANJA MODAL KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Endang Sri Mulatsih (JURNAL KOMPETITIF, 2016)
This research aimed to analyze the influence of General Allocation Fund (DAU), Special Allocation Fund (DAK), Population and the landmass of the regional capital expenditure district/city in South Sumatra province. Data in this research is regional Government Budget at 15 districts/cities in South Sumatra province in 2012-2013 time period. Model analysis in this research is using multiple regression. It can seen that in total General Allocation Fund (DAU), Special Allocation Fund (DAK), Population and the landmass has positive effect to capital expenditure in district/city in Sumatra Selatan Province, meanwhile partially General Allocation Fund (DAU), Special Allocation Fund (DAK) and Population has no effect to capital expenditure but the landmass has positive effect. Keywords: General Allocation Fund, Special Allocation Fund, population, the landmass and Capital Expenditure